The returns to education over time: the Malaysian outlook, 1984-1997. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2004)
The returns to education over time are examined in Riveros (1990) for Chile, Demetriades and Psacharopoulos (1987) for Cyprus, Appleton et al. (1995) for Kenya, Funkhouser (1998) for Costa Rica, Palme and Wright (1998) for Sweden and Duraisamy (2000) for India.